Sexual Dysfunction in Heroin Dependents: A Comparison between Methadone and Buprenorphine Maintenance Treatment - Yee, A.; Danaee, M.; Loh, H.S.; Sulaiman, A.H.; Ng, C.G. (Public Library of Science, 2016)
Introduction: Methadone has long been regarded as an effective treatment for opioid dependence. However, many patients discontinue maintenance therapy because of its side effects, with one of the most common being sexual dysfunction. Buprenorphine is a proven alternative to methadone. This study aimed to investigate sexual dysfunction in opioid-dependent men on buprenorphine maintenance treatment (BMT) and methadone maintenance treatment (MMT). The secondary aim was to investigate the correlation between sexual dysfunction and the quality of life in these patients. Methods: Two hundred thirty-eight men participated in this cross-sectional study. Four questionnaires were used, the Mini International Neuropsychiatric Interview, Opiate Treatment Index, Malay version of the International Index of Erectile Function 15 (Mal-IIEF-15), and World Health Organization Quality of Life-BREF Scale. Multivariate analysis of covariance was used to examine the relationship between MMT and BMT and the Mal-IIEF 15 scores while controlling for all the possible confounders. Results: The study population consisted of 171 patients (71.8%) on MMT and 67 (28.2%) on BMT. Patients in the MMT group who had a sexual partner scored significantly lower in the sexual desire domain (p < 0.012) and overall satisfaction (p = 0.043) domain compared with their counterparts in the BMT group. Similarly, patients in the MMT group without a sexual partner scored significantly lower in the orgasmic function domain (p = 0.008) compared with those in the BMT group without a partner. Intercourse satisfaction (p = 0.026) and overall satisfaction (p = 0.039) were significantly associated with the social relationships domain after adjusting for significantly correlated sociodemographic variables. Conclusions: Sexual functioning is critical for improving the quality of life in patients in an opioid rehabilitation program. Our study showed that buprenorphine causes less sexual dysfunction than methadone. Thus, clinicians may consider the former when treating heroin dependents who have concerns about sexual function.